MicroRNA-181a Is Involved in Methamphetamine Addiction Through the ERAD Pathway - Wang, Yujing; Wei, Tao; Zhao, Wei; Ren, Zixuan; Wang, Yan; Zhou, Yiding; Song, Xun; Zhou, Ruidong; Zhang, Xiaochu; Jiao, Dongliang (Frontiers in Molecular Neuroscience, 2021)
The regulation of microRNA (miRNA) is closely related to methamphetamine (METH) addiction. Past studies have reported that miR-181a is associated with METH addiction, but the mechanism pathways remain elusive. On the basis of our past studies, which reported the endoplasmic reticulum-associated protein degradation (ERAD) mediated ubiquitin protein degradation of GABAAα1, which was involved in METH addiction. The present study, using qRT-PCR and bioinformatics analysis, further revealed that miR-181a may be indirectly responsible for the METH addiction and downregulation of GABAAα1 through the regulation of ERAD.